Influence of dietary tryptophan levels on the growth performance of segregated early-weaned pigs (10 to 20 lb) - Loughmiller, J.A.; Knabe, D.A.; Hongtrakul, K.; O'Quinn, P.R.; Moser, S.; Smith, J.W.II; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 360 pigs (averaging 13 d of age and 9.4 lb) was used to determine the effects of increasing dietary tryptophan:lysine ratio on the growth performance of segregated early-weaned (SEW) pigs. Two apparent digestible lysine levels (1. 15 and 1.50 %) and six apparent digestible tryptophan: lysine ratios (12.5, 15, 17.5, 20, 22.5 and 25%) were fed from d 0 to 16 after weaning. Lysine x tryptophan interactions were observed for ADG and F/G. Increasing the tryptophan: lysine ratio in the low lysine diets improved ADG and F/G in a quadratic manner. Increasing the tryptophan level had no effect in the high lysine diets. Results of this trial indicate that optimal apparent digestible tryptophan: lysine ratio is approximately 15 %.
Keywords: Swine; SEW pig; Tryptophan; Lysine